Experimental study on dynamic viscosity of aqueous-based nanofluids with an addition of ethylene glycol - Wahaizad, Safiei; M. M., Rahman; Musfirah, Abdul Hadi; Maleque, M. A.; Singh, R. (IOP Publishing, 2021)
In this study, the effect of adding different nanoparticles in the mixture of deionised water and ethylene glycol on dynamic viscosity is investigated experimentally. In order to prepare for single nanofluids, the dry nanoparticles of SiO2, Al2O3 and ZrO2 were dispersed into 60% volume of deionised water and 40% volume of ethylene glycol as a base fluid using a two-step method. The experiments were performed in the temperature range of 30°C and 70°C and weight fraction ranging between 0.1wt.% and 1wt%. No surfactant used in preparing the nanofluids. The dynamic viscosity data were collected using DV-II+ Pro Brookfield viscometer. The single, dual-hybrid and tri-hybrid aqueous based nanofluids dynamic viscosity results are explicitly presented. From the results, it is exhibited that nanofluid viscosity decreases with increasing liquid temperature and increases with increasing of nanoparticles volume concentration. The viscosity decreases with increasing of deionised water volume percentage in the base fluid. Zirconia single nanofluid at 1wt.% recorded 2.5 times maximum enhancement of viscosity over the base fluid. The results display that single nanofluids have higher dynamic viscosity compared to hybrid nanofluids.